2011
DOI: 10.3928/1081597x-20101105-02
|View full text |Cite
|
Sign up to set email alerts
|

Biometry of the Cornea in Myopic Chinese Patients

Abstract: Axial length appears to be the main morphological parameter related to myopia. Myopic corneas took the form of a rotationally asymmetric prolate ellipsoid that gradually flattened towards the periphery. The study also provided evidence of symmetry between an individual's right and left corneas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 34 publications
3
10
0
Order By: Relevance
“…Therefore, the fellow corneas of the healthy subjects seem to have similar volumes and 3D configurations. This is consistent with the results of previous studies reporting symmetry in terms of pachymetric data [9,11,13,[36][37][38][39]. Specifically, Prakash et al [13] observed that minimum corneal thickness points in fellow eyes tended to be symmetrical along the vertical midline.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, the fellow corneas of the healthy subjects seem to have similar volumes and 3D configurations. This is consistent with the results of previous studies reporting symmetry in terms of pachymetric data [9,11,13,[36][37][38][39]. Specifically, Prakash et al [13] observed that minimum corneal thickness points in fellow eyes tended to be symmetrical along the vertical midline.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have been conducted to evaluate the level of interocular corneal symmetry in the normal healthy population by analyzing a great variety of parameters provided by different commercial devices used for such purpose [8][9][10][11][12][13][14][15]32,[36][37][38][39]. Specifically, high levels of interocular symmetry have been reported in variables such as corneal curvature [9,10,12,37], central corneal thickness [9,13,37,38], anterior and posterior corneal elevation [10,12,38], corneal astigmatism [9,11,36,39], minimum corneal thickness [10,12,13], corneal aberrations [14], corneal diameter [15], corneal shape factor [37], and even some biomechanical metrics [40]. This is consistent with the results obtained in our sample, as we did not find significant differences between fellow eyes in corneal asphericity, aberrations, pachymetry, and volume.…”
Section: Discussionmentioning
confidence: 99%
“…Dubbelman et al 1 found that the anterior and posterior corneal surfaces were significantly steeper in myopic eyes than in hyperopic eyes. However, some authors report scientific evidence of no significant correlation between corneal curvature and AL 24 and or even a trend opposite 25 to that found in the Dubbelman study. In our study, the presence of a reduced anterior:posterior ratio for corneal curvature may have been related to a steep anterior corneal surface within the normal physiologic range and a posterior cornea with the average curvature as well as to an anterior corneal surface with the average curvature and a flat posterior corneal surface within the normal physiologic range.…”
Section: Discussionmentioning
confidence: 63%
“…There were no significant correlations between Front Km and AL and ACD. Similarly, Bao et al 36 reported no significant correlation between corneal curvature and AL. However, Abolbashari et al 21 reported a correlation between ACD with mean K reading and Back Km.…”
Section: Discussionmentioning
confidence: 95%